4 love petals / Nur Nabilah Athirah Osman - Osman, Nur Nabilah Athirah (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
In an effort t o improve consumer relations, Hati Gift Shop, which was founded in Perlis in 2020 b y Mr. Mohd Latif Bin Ramli, redesigned its l ogo. Acknowledging design flaws, the business resol ved difficul ties with imprecise service representation and poor communication. In or der to address this full y, Hati Gift S hop adopted modifica tions to its name, tagline, and l ogo. The redesign pu t a l ot of effort in to including flor al themes t o emphasize its three main services: supplies, arr angements, and flo wer delivery . Including s ymbolic images in the l ogo— such as bouque ts o f flo wers— became a way t o e xpress the c ompany 's message visually. The purpo se of adding the descript or "bouquets and gift" was t o impr ove the way tha t customers under stood what Ha ti Gift S hop offered. The rebr anding process also included choo sing the name "4 Love Petals," which captures the spirit o f the c ompany. The sl ogan "Memorable delivery o f L ove," which was selected, reaffirmed the dedica tion t o offering a special and remarkable gifting experience. Hati Gift Shop adopted a unique approach to design by fusing genuine flower imagery with cartoons f ound in their ads. This inno vative appr oach, unusual in the flo wer delivery sect or, sough t t o dr aw clients in with its dis tinctiveness. Ha ti Gift Shop might stand out from the c ompetition b y strategically c ombining real flo wer and illustrations in its ad vertising campaigns. This would a ttract t o cus tomers looking for unique and meaningful presents. In conclusion, the rebr anding objective o f Ha ti Gift S hop is t o bec ome a preferred location for people looking for unusual and deeply meaningful gifts in addition t o gorgeous flowers. The organiza tion wants t o be kno wn for its uniqueness, in ventiveness, and the emotional experiences it pr ovides to its clien ts.